2007
DOI: 10.1111/j.1467-6486.2007.00708.x
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effect of CEO Power on the Board Composition–Firm Performance Relationship*

Abstract: Prior studies of the relationship between the composition of boards of directors and firm performance offer equivocal results. Drawing on agency and power circulation theories, we attempt to reduce this equivocality by asserting that CEO power moderates the relationship. Specifically, an outside director dominated board is needed to check a powerful CEO, but monitoring by other executives provides sufficient constraints on CEOs with low power. We used event study methodology to test the effects of the interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
172
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(207 citation statements)
references
References 87 publications
(145 reference statements)
8
172
1
6
Order By: Relevance
“…Dependent resource theorists support large board size and they argue that large board will expose firms to great business connections and critical resources (Dalton, Daily, Ellstrand & John 1999). In addition, large board is likely to have members with diverse background, experiences and who possess great collection of information which may add value to the performance of the firm (Arosa et al 2010;Dalton et al 1999;Combs et al 2007). From agency theory perspective, Jensen (1994) declared that large board is less effective than small board.…”
Section: Board Sizementioning
confidence: 99%
See 3 more Smart Citations
“…Dependent resource theorists support large board size and they argue that large board will expose firms to great business connections and critical resources (Dalton, Daily, Ellstrand & John 1999). In addition, large board is likely to have members with diverse background, experiences and who possess great collection of information which may add value to the performance of the firm (Arosa et al 2010;Dalton et al 1999;Combs et al 2007). From agency theory perspective, Jensen (1994) declared that large board is less effective than small board.…”
Section: Board Sizementioning
confidence: 99%
“…For instance, the 11 of 14 board members of Enron were outside directors and more than 50% of WorldCom's board were also outside directors (Rashid 2010). Combs et al (2007) declared that in practice outside directors largely depended on the executive and their independence is weakened because they are subjected to manipulation of the executive. Despite these shortcomings, scholars have suggested that board composition with outsiders is comparatively better than board without outsiders in protecting the interest of the shareholders and boost firms performance (Combs et al 2007;Jensen & Meckling 1976).…”
Section: Outside Directorsmentioning
confidence: 99%
See 2 more Smart Citations
“…En los 90´s: Denison (1990) y Porras y Collins (1994), y en el siglo XXI: Hitt, Ireland y Hoskinsson (2004), Daft (2005) y Combs et al (2007) entre otros, vienen afirmando que la diferencia entre organizaciones exitosas y no exitosas estriba en el compromiso de la gerencia en el manejo de una serie de "variables suaves", que se han agrupado en la expresión de cultura, ambiente o clima laboral u organizacional, que sirven para dinamizar las condiciones de trabajo tanto internas como externas y que a su vez inciden directamente y de manera contundente en los resultados empresariales.…”
Section: Primera Parte Preliminaresunclassified